Valorising mesquite biochar as a sustainable adsorbent for wastewater treatment: a critical review - Al Saadi, Amal; Al-Yahmadi, Ismail; Al-Rashdi, Nabila; Mohamed, Izzeldin I.; Al-Busaidi, Intisar K. (Frontiers in Chemical Engineering, 2026)
The increasing demand for sustainable wastewater treatment methods has driven interest in biochar as an economical and eco-friendly adsorbent. Among various biomass sources, mesquite, an invasive species prevalent in arid and semi-arid areas represents a renewable yet underexploited material for biochar synthesis. This review critically examines the use of mesquite-based biochar for wastewater purification. Particular attention is given to how production parameters, including pyrolysis temperature, heating rate, and particle size, influence material properties and treatment performance reported in the literature. Mesquite biochar displays high surface area generally ranging from 50 to >800 m2/g, alkalinity, and porosity, facilitating the effective removal of heavy metals, organic contaminants, and nutrients through mechanisms like electrostatic attraction, ion exchange, and surface complexation. Chemical activation, especially using alkaline agents, further enhances its adsorption efficiency. However, adsorption performance varies considerably between studies, largely due to differences in production conditions and the absence of consistent testing methodologies. In addition to pollutant elimination, mesquite biochar aids in carbon sequestration and soil fertility improvement, contributing to wider ecological benefits. Economic feasibility and sustainability considerations are also discussed, alongside persistent research gaps related to large-scale production, regeneration efficiency, and long-term use. Overall, mesquite biochar shows strong potential as a sustainable and efficient adsorbent for wastewater management, supporting global goals for resource recovery and circular economy. The development of metal-modified biochars with iron functionalization represents a new direction for wastewater treatment because these systems combine adsorption with redox and photocatalytic functions.